Nanostructured transition metal oxide (TMO) for electrochemical devices - Khoo, Eugene (2012)
This thesis focuses on the reaction mechanism and kinetic study of electrochemical reactions in transition metal oxide, which include electrical double layer (EDL), surface charge transfer reaction and diffusion controlled redox reaction. Modifications on the oxide have been designed to study the effect on the reactions and hence the electrochemical performances. These modifications include the variation in oxide morphology and dimension, conductive metal doping and altering of oxide lattice structure. The key parameters governing the electrochemical reactions in transition metal oxides are the oxide-electrolyte interface, electronic conductivity, ion diffusion distance, ion diffusion pathway and ion intercalation site. With detailed studies in the optical and electrochemical performances of the modified oxide, the effects of altering these parameters were evaluated. The increase in oxide-electrolyte interfacial area was achieved through controlling the oxide morphology and dimension. This has promoted the surface dependent reaction (including EDL and surface charge transfer reaction). As a result, higher electrochemical activity can be achieved and hence higher capacitance and rate capability. On the other hand, the electronic conductivity was shown to be improved through doping conductive metal into the oxide lattice. The enhancement in the electronic conductivity improves charge transfer rate in the oxide, resulting in better rate capability and capacitance. Ion diffusion strongly affects the diffusion controlled redox reaction in oxide lattice. The ion diffusion distance and diffusion pathway are the two basic factors of ion diffusion in oxide lattice. In this thesis, the shortening of diffusion distance has been achieved by reducing the oxide dimension while different types of diffusion pathways with shortened diffusion distances were generated through the altering of oxide lattice structure. The last parameter is the ion intercalation sites, which were tailored through controlling the oxide lattice structure. By having large amount of easy accessible intercalation sites, the chemisorptions of cation at oxide-electrolyte interface and the ion intercalation in oxide lattice were greatly promoted. This increases the total amount of redox reaction in the oxide. In parallel to the mechanism studies, these modified oxides were employed as the electrodes of electrochromic (EC) device and supercapacitor to examine their EC properties and the charge storage performances.